Powerful Prose How Textual Features Impact Readers - Pöhls, R. L. Victoria (Lettre, 2021)
What makes a reading experience »powerful«? This volume brings together literary scholars, linguists, and empirical researchers to elucidate the effects and reader responses to investigate just that. The thirteen contributions theorize this widely-used, but to date insufficiently studied notion, and provide insights into the therefore still mysterious-seeming power of literary fiction. The collection investigates a variety of stylistic as well as readerly and psychological features responsible for short- and long-term effects - topics of great interest to those interested or specialized in literary studies and narratology, (cognitive) stylistics, empirical literary studies and reader response theory.